An Economic and Econometric Analysis of the Impact of Key Economic Variables on Cotton Production in Iraq - Abdullah, Dawood Fahad; Al-Tamimi, Abbas Abd Ahmed (American Journal of Botany and Bioengineering, 2026)
Cotton remains an essential crop for Iraq’s industry, contributing substantially to its gross domestic product, employment, and input to local industry. Despite its importance, cotton production in Iraq was subject to fluctuations between 1995 and 2021, averaging a land area of 13,690 hectares (range from 3 to 26,995 hectares) and averaging a production level of 24,078 tons (range from 3 to 45,278 tons). This study examined the influence of some major economic factors, including the land area, gross domestic product, crop price index, and productivity, on cotton production in Iraq through a time-series econometric model. The results from the unit roots tests, including the Augmented Dickey-Fuller and Phillips-Perron tests, showed that the variables were non-stationary at their level but became stationary after first differencing. This study adopted the Autoregressive Distributed Lag model, which was appropriate for this study due to its ability to capture the short-run and long-run effects, especially for small samples. The results showed that the variables explained about 94% of the fluctuations in cotton production, thereby indicating the existence of a long-run equilibrium relationship among the variables. The error term was -0.339, which indicated that deviations from equilibrium correct themselves after a period of about three years. The Gross Domestic Product was found to have a significant positive influence on cotton production in Iraq, while the crop price index was seen to positively influence cotton production, with a small degree of responsiveness for farmers in the short-run as well as the long-run. Productivity was seen to positively influence cotton production in Iraq. This study therefore highlights the need for the use of cointegration and error correction models for more reliable results compared to regression models. It therefore recommended that the government should ensure that cotton farmers are provided with essential items, irrigation systems, as well as price support, while at the same time improving their productivity through integrated strategies for marketing and agricultural credit to stabilize cotton production in Iraq. From the results obtained, this study showed that for cotton production in Iraq to improve, there was a need for economic interventions to ensure that cotton was not neglected.